2021
DOI: 10.1155/2021/1174452
|View full text |Cite
|
Sign up to set email alerts
|

Research of Inonotus obliquus Oligosaccharide in Prevention of Hyperlipidemia

Abstract: In this study, hot water was used to extract Inonotus obliquus oligosaccharide. DEAE-cellulose and Sepharose G-200 were used to purify Inonotus obliquus oligosaccharide. Inonotus obliquus oligosaccharide IOP-2A was obtained. Its molecular weight Mw is about 1000 Da. The monosaccharide composition and molar ratio were glucose : xylose : galactose : mannose = 54.1 : 13.6 : 13.2 : 6.7. In addition, it also contains a small amount of galactose, gluconic acid, rhamnose, and fucose. IOP-2A contained mainly β-glycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Hypolipidemic effects were also observed in the 250 mg/kg and 500 mg/kg I. obliquus aqueous extract treatment groups, with decreased TC, TG, and LDL-C and increased liver glycogen and HDL-C in high-fat diet-inducedC57BL/6 mice via the regulation of the PI3K/Akt and AMPK/ACC signalling pathways [ 208 ]. Similar hypolipidemic effects were also reported in oligosaccharides of I. obliquus via modification of the intestinal bacteria in high-fat fed mice in which the ratio between the population of Firmicutes to Bacteroidetes faecal flora was reduced in treated groups, reducing the production of fatty acids and thus lowering blood lipids [ 209 ].…”
Section: Health-promoting Propertiessupporting
confidence: 70%
“…Hypolipidemic effects were also observed in the 250 mg/kg and 500 mg/kg I. obliquus aqueous extract treatment groups, with decreased TC, TG, and LDL-C and increased liver glycogen and HDL-C in high-fat diet-inducedC57BL/6 mice via the regulation of the PI3K/Akt and AMPK/ACC signalling pathways [ 208 ]. Similar hypolipidemic effects were also reported in oligosaccharides of I. obliquus via modification of the intestinal bacteria in high-fat fed mice in which the ratio between the population of Firmicutes to Bacteroidetes faecal flora was reduced in treated groups, reducing the production of fatty acids and thus lowering blood lipids [ 209 ].…”
Section: Health-promoting Propertiessupporting
confidence: 70%
“…Oligosaccharides isolated from I. obliquus also provided protection against hyperlipidaemia. Kunming mice were fed a high-fat diet (HFD) for 1 week, then allowed to eat and drink freely with I. obliquus oligosaccharide (IOP-2A) administered by gavage in designated groups (Wu et al 2021 ). Biochemical analysis of mice serum showed that IOP-2A is able to ameliorate dyslipidaemia by decreasing TC, TG, and LDL-C levels while increasing HDL-C concentrations.…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%